Subjective Preference Study on IACC for National Music Hall - Guo, Tian Kui (Applied Mechanics and Materials, 2013)
IACC is an important objective acoustics parameter for evaluating hall acoustics. In order to find out subjective preference value or range of IACC for Chinese national music, under Ando’s hall acoustics theory, by keeping other acoustics parameters unchanged, subjective preference test on IACC was completed by paired-comparison method using headphone reproduction. Firstly, depending on measured binaural impulse responses with very low IACC, by adjusting correlation coefficient, five pairs of binaural impulse responses with different and equal-spaced IACC were derived and then convolved with CD musics including solo and tutti played by Chinese national musical instruments, thus auralization binaural signals were produced. The test’s results indicate that when IACC is between 0.15 and 0.41,acoustics for Chinese national music hall is preferable subjectively，accordingly, subjective preference range for IACCE3 is between 0.19 and 0.46.